Digital Taxation Challenges in the Global Economy: Lessons from OECD and G20 Practices - Loso Judijanto; Rina Nopianti; Prastika Suwandi Tjeng; Rudy Surbakti; Nong Chai (Journal Markcount Finance, 2025)
The rapid growth of digital economies has created complex challenges for national tax systems, necessitating a reassessment of taxation policies and practices. Multinational digital enterprises often operate across borders, creating difficulties in allocating taxable profits and ensuring fair tax contributions. The Organization for Economic Cooperation and Development (OECD) and G20 countries have developed frameworks and initiatives to address these challenges, yet implementation and harmonization remain uneven. This study aims to examine the key challenges of digital taxation in the global economy, drawing lessons from OECD and G20 practices, and to identify strategies for improving policy effectiveness and international cooperation. A qualitative research methodology is employed, combining document analysis of OECD and G20 reports with interviews of tax experts and policymakers. The results indicate that while international frameworks provide valuable guidance, discrepancies in national implementation, divergent regulatory approaches, and the rapid evolution of digital business models hinder consistent taxation. The study concludes that achieving equitable and effective digital taxation requires enhanced international collaboration, adaptive regulatory mechanisms, and continual monitoring of digital business developments. Lessons from OECD and G20 practices highlight the importance of coordinated policy frameworks to minimize tax avoidance and ensure fair contribution of digital enterprises globally.